Assessing Atraumatic Versus Conventional Restorative Treatment For Dental Caries In Deciduous Molars: A Comparative Study - Sunaila Naz; Syed Atta Ullah Shah; Farhat Gul; Fahad Salim Khan; Rozina Sattar; Talha Asad Khan (Pakistan Journal of Medicine and Dentistry)
Background: Dental caries is common problem seen in children. Treatment options such as atraumatic and conventional restorative techniques are usually performed among such children. This study aimed to determine the success rate associated with these restorative techniques.